Stakeholder engagement, government policy, and tourist satisfaction - Jumadi; Adhifa, Muhammad Nugroho Hariadi Nur; Amelia, Amanda; Ashiva, Devitri Salsa (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2024)
The tourism industry has a complex relationship between geography, and all-natural resources, human, so tourism can create problems in human life. Good management in the tourism industry can create benefits for the nation's economy such as foreign exchange income, business development, and employment opportunities. For the optimum goals, the tourism industry can establish good relations with stakeholders and government policy support. Aim to the research on the evaluation of the effect of stakeholder engagement in tourism development and government policy on tourist satisfaction in the Indonesian tourism industry. This research is based on quantitative to test the hypothesis affecting stakeholder engagement in tourism development and government policy on the Indonesian tourism industry. The sample size of the research 250 with propulsive sampling and the main instrument is a questionnaire. The data analysis to use examine hypothesis with structural equation modelling Amos 20 version. The result of the investigations shows that the stakeholder engagement in tourism development has not been able to provide a level of tourist satisfaction, but the government policies can be influenced by tourist satisfaction.